Prescriptive internalisation as an axiological fundament of meaning the forest as an eco-value - Łukaszewska, Katarzyna (Studia Ecologiae et Bioethicae, 2019)
Internalisation, i.e. incorporation of axiological contents, is concurrent with gaining skills of a higher moral standard. In this process, objective values became the source of responsibility. Internalisation of axiological requirements stemming from eco-values is the most effective type of obligation due to its prescriptive nature: it is impossible not to keep a promise made to oneself without experiencing the loss of the given value. In this context, the internalised eco-values prescriptively influence the person whose sense of responsibility becomes stronger as the value becomes further internalised. Therefore, the forest, as an example of an eco-value, takes on an absolute nature only when prescriptive internalisation occurs – i.e. when the source of moral obligation is not so much the ecological necessity but an autotelic value.